KORESPONDENSI KONSEPTUAL ANTARA RANAH SUMBER DAN RANAH TARGET DALAM UNGKAPAN METAFORIS DI SURAT PEMBACA HARIAN SUARA MERDEKA - Nirmala, Deli (Faculty of Humanities, Diponegoro University, 2012)
This paper is showing the conceptual correspondences between the source and target of the metaphorical expressions used in letters to editors of Suara Merdeka Daily Newspapers. The data are the metaphorical expressions found in the letters to editors of Suara Merdeka Daily Newspapers, and selected by purposive sampling techniques. The data were collected by using non-participant observation with note-taking techniques. They are classified according to the motivation underlying the metaphors inferenced from the metaphorical expressions used. They were analyzed by using referential identity method, distributional method with substitution and paraphrasing techniques, and abductive inferential method. The methods were used to show how the possible cognitive process is activated when the metaphorical expressions used. The results show that the conceptual correspondence is shown by using the strategy of association to show the motivation underlying the metaphors inferenced from the metaphorical expressions used. The motivation underlying the metaphors is the similarity in characteristics, power, attribute, and the bodily experience. Keywords: conceptual correspondences, metaphorical expressions, strategy of association